Asymmetric Total Synthesis of Aglacins A, B, and E. Issue 30 (22nd June 2021) - Xu, Mengmeng; Hou, Min; He, Haibing; Gao, Shuanhu
Abstract: An asymmetric photoenolization/Diels–Alder (PEDA) reaction between electron‐rich 2‐methylbenzaldehydes and unsaturated γ‐lactones was developed to directly construct the basic tricyclic core of aryltetralin lactone lignans. This methodology enabled the first asymmetric total synthesis of aglacins A, B, and E and revision of the absolute configuration of these natural lignans. The strategy was also used to prepare the naturally occurring aryldihydronaphthalene‐type lignans (−)‐7, 8‐dihydroisojusticidin B and (+)‐linoxepin in four and six steps, as well as 27 natural‐product‐like molecules containing a C8′ quaternary center. We believe that the synthetic aglacins and small‐molecule library provide new opportunities to carry out the SAR studies of the podophyllotoxin family of natural products. Abstract : An asymmetric photoenolization/Diels–Alder (APEDA) reaction was developed for the asymmetric total synthesis of the aryltetralin cyclic ether lignans aglacins A, B, and E (see scheme) and enabled revision of the absolute configuration of these natural products. The strategy was also used to synthesize the aryldihydronaphthalene‐type lignans (−)‐7, 8‐dihydroisojusticidin B and (+)‐linoxepin and to build a small library of lignans (27 members).